2010
DOI: 10.1016/j.brainres.2009.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Role of orexin/hypocretin in dependence and addiction

Abstract: The orexins (or hypocretins) are hypothalamic neuropeptides that have been implicated in a variety of behaviors ranging from feeding to sleep and arousal. Evidence from animal models suggests a role for orexins in reward processing and drug addiction. In this review, we discuss orexin’s interaction with the mesocorticolimbic reward pathway and the effects of drugs of abuse on the orexin system. We further review models of drug dependence and addiction and describe behavioral alterations that are seen when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 81 publications
4
63
0
2
Order By: Relevance
“…6; one-way ANOVA: F 3,24 = 11.56, P < 0.01), suggesting that unopposed dynorphin actions within this brain area attenuate cocaine reward. These results appear to be at variance with those that have demonstrated the absence of intra-VTA SB334867 on cocaine self-administration in low-effort fixed ratio 1 (FR1) schedules of reinforcement (40). However, several reports have shown that as task demands increase, SB334867 is more effective in reducing drug taking (2,33).…”
Section: Orexin and Dynorphin Can Exert Balanced Opposing Effects Onmentioning
confidence: 49%
See 1 more Smart Citation
“…6; one-way ANOVA: F 3,24 = 11.56, P < 0.01), suggesting that unopposed dynorphin actions within this brain area attenuate cocaine reward. These results appear to be at variance with those that have demonstrated the absence of intra-VTA SB334867 on cocaine self-administration in low-effort fixed ratio 1 (FR1) schedules of reinforcement (40). However, several reports have shown that as task demands increase, SB334867 is more effective in reducing drug taking (2,33).…”
Section: Orexin and Dynorphin Can Exert Balanced Opposing Effects Onmentioning
confidence: 49%
“…Further, the present experiments focus on the VTA and cannot rule out the possibility that the effects of orexin and dynorphin may not be dichotomous in other structures or that the VTA is the only structure in which orexin-dynorphin interactions influence behavior. For instance, there is evidence that orexin is involved in the stress response and may participate alongside dynorphin to engender negative affective states that accompany drug withdrawal (40,47). Clearly, additional work is necessary to determine the circumstances, anatomical loci, and mechanisms that appear to permit concerted vs. opposing actions of orexin and dynorphin in different behavioral paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of orexin has been shown to affect multiple reward-seeking behaviors, including operant responding for high-fat pellets and sucrose, conditioned place preference (CPP) for food, cue-induced reinstatement of extinguished sucroseseeking, and food-reinforced responding under both variable and progressive ratio schedules of reinforcement (Harris et al, 2005;Cason et al, 2010;Sharf et al, 2010). These studies use the partial OX 1 SORA SB-334867 to suggest the involvement of OX 1 receptors in reward-based feeding.…”
Section: A Central Modulation Of Behavior and Physiology By Orexin Smentioning
confidence: 99%
“…Borgland et al (2006) expanded upon these studies and linked orexin signaling with synaptic plasticity in VTA dopamine neurons and behavioral sensitization to cocaine. On the basis of these studies, a vast body of preclinical research has evolved around orexin signaling in addictive behaviors Lawrence, 2010;Sharf et al, 2010;Zhou et al, 2011). Together, these studies have indicated the potential for blocking drug-seeking behaviors through antagonism of orexin signaling, suggesting orexin receptor antagonists as possible therapeutics for treating addiction to a variety of abusive drugs, including cocaine, amphetamine, alcohol, and morphine.…”
Section: A Central Modulation Of Behavior and Physiology By Orexin Smentioning
confidence: 99%
“…In parallel, evidence has accumulated that demonstrates an involvement of OX signaling via OX1R in reward pathways associated with drug dependence (Sharf et al, 2010). The role of the OX1R in emotional behavior is emerging .…”
Section: Introductionmentioning
confidence: 99%